Hereditary mixed polyposis syndrome is caused by a 40-kb upstream duplication that leads to increased and ectopic expression of the BMP antagonist GREM1 - Jaeger, E; Leedham, S; Lewis, A; Segditsas, S; Becker, M; Cuadrado, P; Davis, H; Kaur, K; Heinimann, K; Howarth, K; East, J; Taylor, J; et al. (2012)
Hereditary mixed polyposis syndrome (HMPS) is characterized by apparent autosomal dominant inheritance of multiple types of colorectal polyp, with colorectal carcinoma occurring in a high proportion of affected individuals. Here, we use genetic mapping, copy-number analysis, exclusion of mutations by high-throughput sequencing, gene expression analysis and functional assays to show that HMPS is caused by a duplication spanning the 3′ end of the SCG5 gene and a region upstream of the GREM1 locus. This unusual mutation is associated with increased allele-specific GREM1 expression. Whereas GREM1 is expressed in intestinal subepithelial myofibroblasts in controls, GREM1 is predominantly expressed in the epithelium of the large bowel in individuals with HMPS. The HMPS duplication contains predicted enhancer elements; some of these interact with the GREM1 promoter and can drive gene expression in vitro. Increased GREM1 expression is predicted to cause reduced bone morphogenetic protein (BMP) pathway activity, a mechanism that also underlies tumorigenesis in juvenile polyposis of the large bowel. © 2012 Nature America, Inc. All rights reserved.